2023
DOI: 10.3390/app13148537
|View full text |Cite
|
Sign up to set email alerts
|

A New Hybrid Algorithm Based on Improved MODE and PF Neighborhood Search for Scheduling Task Graphs in Heterogeneous Distributed Systems

Abstract: Multi-objective task graph scheduling is a well-known NP-hard problem that plays a significant role in heterogeneous distributed systems. The solution to the problem is expected to optimize all scheduling objectives. Pretty large state-of-the-art algorithms exist in the literature that mostly apply different metaheuristics for solving the problem. This study proposes a new hybrid algorithm comprising an improved multi-objective differential evolution algorithm (DE) and Pareto-front neighborhood search to solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Additionally, competition arises among local governments as they strive to distinguish their jurisdictions through fiscal policies that attract mobile economic factors [49]. This competition, known as fiscal competition, incentivizes local governments to minimize taxes and maximize public expenditures to enhance the appeal of their jurisdictions for investments, skilled workers, and businesses [133][134][135].…”
Section: Fiscal Decentralization and Local Governmentsmentioning
confidence: 99%
“…Additionally, competition arises among local governments as they strive to distinguish their jurisdictions through fiscal policies that attract mobile economic factors [49]. This competition, known as fiscal competition, incentivizes local governments to minimize taxes and maximize public expenditures to enhance the appeal of their jurisdictions for investments, skilled workers, and businesses [133][134][135].…”
Section: Fiscal Decentralization and Local Governmentsmentioning
confidence: 99%
“…In addition, to minimize the cost of long-distance energy transmission, it is suggested that this hybrid system is located near the supermarket. To solve the bi-objective problem, first, a PSO-based algorithm was developed [47] and, next, HOMER Pro software was used to simulate the considered hybrid system, since this software has been frequently used in the field of renewable energy systems. The HOMER Pro software uses sophisticated optimization algorithms, which simulate users' defined systems in a single run.…”
Section: Introductionmentioning
confidence: 99%